2015
DOI: 10.1007/s10681-014-1341-8
|View full text |Cite
|
Sign up to set email alerts
|

Response of maize population “Longe5” to two cycles of modified S1 recurrent selection for resistance to maize weevil

Abstract: The maize weevil (Sitophilus zeamais Mostch.) is one of the most damaging storage pests causing significant reductions in grain weight and quality in tropical and subtropical regions. The current study determined the effectiveness of two cycles of modified S 1 recurrent selection towards the improvement of weevil resistance in the maize variety ''Longe5''. Grain yield and resistance to Turcicum leaf blight, grey leaf spot and rust diseases, which occurred naturally at the time of experimentation, were also eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Maize weevil mortality was not significantly different among the genotypes. This is consistent with results by Dhliwayo et al (2005) and Kasozi et al (2015) but in contrast to findings by Nhamucho et al (2017) who reported significant differences in maize weevil mortality among Mozambican local and improved maize genotypes. Mortality maybe attributed to presence of a fluorescent pericarp with high concentration of hydroxycinnamic acid ( Serratos et al, 1987 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Maize weevil mortality was not significantly different among the genotypes. This is consistent with results by Dhliwayo et al (2005) and Kasozi et al (2015) but in contrast to findings by Nhamucho et al (2017) who reported significant differences in maize weevil mortality among Mozambican local and improved maize genotypes. Mortality maybe attributed to presence of a fluorescent pericarp with high concentration of hydroxycinnamic acid ( Serratos et al, 1987 ).…”
Section: Discussionsupporting
confidence: 91%
“…Assessment of grain weight loss among hybrids revealed significant variation suggesting presence of genotypic differences in maize weevil resistance in this germplasm. Similar findings were reported by Tefera et al (2011) , Masasa et al (2013) , Zunjare et al (2014) , Derera et al (2014) and Kasozi et al (2015) in studies with different types of maize germplasm. The large variation for grain weight loss for these germplasm means that the selection could be an effective strategy for maize weevil resistance improvement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Kasozi et al (2015) used two cycles of modified S1 recurrent selection to study resistance to maize weevil in maize. The authors found that the modified S1 recurrent selection was effecttive in improving Longe5 for maize weevil resistance.…”
Section: Conventional Breeding For Weevil Resistance In Sorghummentioning
confidence: 99%